A descriptive catalogue of the music of Charles Ives - Sinclair, James B. (Yale University Press, 1999)
"This catalogue serves to describe the music manuscripts in the Charles Ives Papers, MSS 14, in the Irving S. Gilmore Music Library of Yale University. The remainder of the Ives Papers are described in Vivian Perlis, Charles Ives Papers (New Haven: Yale University Music Library, 1983)."--Title screen